A comparison of unhealthy lifestyle practices among adults with hypertension aware and unaware of their hypertensive status: results from the 2013 WHO STEPS survey in Burkina Faso - Jeoffray Diendéré; Jean Kaboré; William Kofi Bosu; Jérome Winbetouréfâ Somé; Franck Garanet; Pingdéwendé Victor Ouédraogo; Abdoul Aziz Savadogo; Athanase Millogo; Augustin Nawidimbasba Zeba (BMC, 2022)
Abstract Background We compared the prevalence of unhealthy lifestyle factors between the hypertensive adults who were aware and unaware of their hypertensive status and assessed the factors associated with being aware of one's hypertension among adults in Burkina Faso. Methods We conducted a secondary analysis of data from the World Health Organization Stepwise approach to surveillance survey conducted in 2013 in Burkina Faso. Lifestyle factors analysed were fruits and vegetables (FV) consumption, tooth cleaning, alcohol and tobacco use, body mass index and physical activity. Results Among 774 adults living with hypertension, 84.9% (95% CI: 82.2-87.3) were unaware of their hypertensive status. The frequencies of unhealthy lifestyle practices in those aware vs. unaware were respectively: 92.3% vs. 96.3%, p = 0.07 for not eating, at least, five FV servings daily; 63.2% vs. 70.5%, p = 0.12 for not cleaning the teeth at least twice a day; 35.9% vs. 42.3%, p = 0.19 for tobacco and/or alcohol use; 53.9% vs. 25.4%, p = 0.0001 for overweight/obesity and 17.1% vs, 10.3%, p = 0.04 for physical inactivity. In logistic regression analysis, older age, primary or higher education, being overweight/obese [adjusted odds ratio (aOR) = 3.2; p < 0.0001], intake of adequate FV servings daily (aOR = 2.9; p = 0.023) and non-use of alcohol and tobacco (aOR = 0.6; p = 0.028) were associated with being aware of one's hypertensive status. Conclusion Undiagnosed hypertension was very high among Burkinabè adults living with hypertension. Those aware of their hypertension diagnosis did not necessarily practise healthier lifestyles than those not previously aware of their hypertension. Current control programmes should aim to improve hypertension awareness and promote risk reduction behaviour.